Key parameters of the swimming start and their relationship to start performance - Tor, E.; Pease, D. L.; Ball, K. A. (Journal of Sports Sciences, 2015)
The swimming start is typically broken into three sub-phases; on-block, flight, and underwater phases. While overall start performance is highly important to elite swimming, the contribution of each phase and important technical components within each phase, particularly with the new kick-start technique, has not been established. The aim of this study was to identify technical factors associated with overall start performance, with a particular focus on the underwater phase. A number of parameters were calculated from 52 starts performed by elite freestyle and butterfly swimmers. These parameters were split into above-water and underwater groupings, before factor analysis was used to reduce parameter numbers for multiple regression. For the above-water phases, 81% of variance in start performance was accounted for by take-off horizontal velocity. For the underwater water phase, 96% of variance was accounted for with time underwater in descent, time underwater in ascent and time to 10 m. Therefore, developing greater take-off horizontal velocity and focussing on the underwater phase by finding the ideal trajectory will lead to improved start performance.